Study of Correlation of Severity and Quality of Life in Patients with Congenital Ichthyosis - Hemrajani, Priyanka; Sharma, Mona; Dhali, Tapan Kumar; B.C., Sharath Kumar (Nepal Journal of Dermatology, Venereology & Leprology, 2022)
Introduction: Congenital ichthyosis is a disorder of cornification of skin with various cutaneous symptoms. Quality of life is a subjective perception of patients regarding their disease status and treatment received. Dermatological disorders have poor quality of life associated with them as any other systemic disease. Objective : The present study was conducted to assess the quality of life among patients of congenital ichthyosis, so that suitable remedial measures may be devised based on the same. Materials and Methods: It was a hospital based cross-sectional study with total 120 patients enrolled for study duration of one year .Children’s Dermatology Quality Life Index (CDLQI) questionnaire was used to assess the quality of life among patients. Global disease severity scale and VAS scale for severity of ichthyosis was used along with recording of socio-demographic details. Results: With a response rate of 87%, the sample size comprised of 104 subjects, aged between 0-15 years. Females outnumbered the sample by more than 2/3rd. ‘Symptoms and feelings’ was the most affected domain in the CDLQI. Itching, female gender and presence of scales were significant predictors of poor quality of life scores. Conclusion: The present study shows the epidemiological correlation of patients with congenital ichthyosis and the predictors of poor quality of life score. Regular subjective assessment of quality of life among patients should be included in routine clinic visits, as counselling plays a very important role in these patients.